Cinnamon twisted - Bolton, Ginger (Bolton, Ginger. Deputy Donut mystery, 2023)
When a recent customer turns up dead, donut café owner Emily Westhill becomes the prime suspect after an envelope addressed to her is discovered at the murder scene.